Error correction models for fractionally cointegrated time series - Ingolf Dittmann (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2000)
This note provides a proof of Granger's (1986) error correction model for fractionally cointegrated variables and points out a necessary assumption that has not been noted before. Moreover, a simpler, alternative error correction model is proposed which can be employed to estimate fractionally cointegrated systems in three steps.
Keywords: C32; 519; error correction model; fractional cointegration; Granger Representation Theorem; Theorie; Fehlerkorrekturmodell